Le Zebu Brahma au Cameroun (Premiers resultats de son introduction en Adamawa) - Mandon, A. (1957)
Describes breed quality improvement scheme started in 1952 on Adamawa plateau, Cameroun. Zebu Brahma imported from USA were crossed with Fulani breed to improve the precocity, weight and economic value of the Fulani. The first generation crossed breed, the Prewakwa showed more precocity and a higher live weight than the Fulani of the same age. The Prewakwa were as resistant to the local conditions as the Fulani. The second generation, the Wakwa were obtained from crossing Prewakwa between themselves. The scheme attained its objective and won the support of many native stockowners.